Pendampingan Pastoral dengan Pendekatan Behavioral untuk Mengatasi Kenakalan Anak Disabilitas Daksa di Desa Tinada Kabupaten Pakpak - Nopita Solin (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research aims to find out what factors cause delinquency in children with physical disabilities and pastoral care using a behavioral approach that is relevant to dealing with delinquency in children with physical disabilities. The research was carried out using a qualitative approach involving pastoral case studies of a number of children with physical disabilities who experienced naughty behavior. Data was collected through participant observation, interviews with children, parents, and pastoral assistants, and documentation analysis. The research results show that pastoral care using a behavioral approach is able to make a positive contribution in managing the naughty behavior of children with disabilities. This research provides an in-depth understanding of the importance of pastoral care integrated with a behavioral approach in helping children with disabilities manage their naughty behavior. The practical implication of these findings is the development of more structured and evidence-based mentoring programs to support the holistic development of children with disabilities.